2014
DOI: 10.1016/j.immuni.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Protect T Cells against NK Cell Attack Mediated by the Activating Receptor NCR1

Abstract: Direct type I interferon (IFN) signaling on T cells is necessary for the proper expansion, differentiation, and survival of responding T cells following infection with viruses prominently inducing type I IFN. The reasons for the abortive response of T cells lacking the type I IFN receptor (Ifnar1(-/-)) remain unclear. We report here that Ifnar1(-/-) T cells were highly susceptible to natural killer (NK) cell-mediated killing in a perforin-dependent manner. Depletion of NK cells prior to lymphocytic choriomenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
204
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 45 publications
17
204
3
Order By: Relevance
“…Prior studies have shown that type I IFN can signal CD8 T cells directly during the expansion phase to promote their survival in memory populations (50,51). It is required for induction of CD8 T cell responses with certain infections, such as lymphocytic choriomeningitis virus (52,53), and this effect was recently shown to be through type I IFN signaling to CD8 T cells in the early phases of proliferation, which prevents expression of the NCR1 receptor that would otherwise facilitate NK cell-mediated killing of these cells (54,55 Intracellular cytokine staining. Spleens were harvested and restimulated as described previously (9), using the immunodominant SIVGag peptides AL11 and DD13 (DRFYKSLRAEQTD) (65) restricted by MHC class I and class II, respectively (each at 2 μg/ml), or (b) full-length SIV-Gag protein (20 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that type I IFN can signal CD8 T cells directly during the expansion phase to promote their survival in memory populations (50,51). It is required for induction of CD8 T cell responses with certain infections, such as lymphocytic choriomeningitis virus (52,53), and this effect was recently shown to be through type I IFN signaling to CD8 T cells in the early phases of proliferation, which prevents expression of the NCR1 receptor that would otherwise facilitate NK cell-mediated killing of these cells (54,55 Intracellular cytokine staining. Spleens were harvested and restimulated as described previously (9), using the immunodominant SIVGag peptides AL11 and DD13 (DRFYKSLRAEQTD) (65) restricted by MHC class I and class II, respectively (each at 2 μg/ml), or (b) full-length SIV-Gag protein (20 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Several NK receptors have been shown to participate in this process, especially NKG2D and NKp46. 23,31 It has been shown that during the early stages of anti-LMCV response, CTLs can escape NK surveillance by increasing the expression of major histocompatibility complex-I inhibitory NK ligands and by decreasing the expression of activating NK-receptor ligands in a type I IFN-dependent process. 31,32 In our study, by using either BM reconstituted or conditional knockout mice, we show that (1) the presence of NK-cytotoxic-proficient cells restrains the accumulation of LCMV-specific CD8 T cells, and (2) that defective NK-cell cytotoxicity correlates with a higher proliferation rate of antigen-specific CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…43 Another example of this shielding applies also to CD8 T cells expressing CD48 that inhibit NK cells through interaction with 2B4 (CD244). 44,45 We found no evidence that NK cells were regulating the size of the CD8 T cell pool, as shown in Figure 4A, by killing activated alloreactive CD8 T cells because CD8 T cell counts were not affected in the absence of NK cells.…”
Section: Discussionmentioning
confidence: 80%